Cavity designs for nitride VCSELs with dielectric DBRs operating efficiently at different temperatures. (December 2020) - Sarzała, Robert P.; Śpiewak, Patrycja; Nakwaski, Włodzimierz; Wasiak, Michał
Highlights: m -plane tunnel-junction GaN-based VCSELs with dielectric DBRs are simulated. TJ GaN-based VCSEL with the optimum number of pairs in the top DBR was designed. The designed VCSEL enable stable operation at high temperatures. Wider metallization allows for around 1.5-fold reduction in thermal resistance. Abstract: This study set out to analyze the performance of modern nitride GaN-based tunnel-junction vertical-cavity surface-emitting lasers (VCSELs) at various ambient and elevated temperatures, with the aid of an advanced self-consistent optical-electrical-recombination-thermal model. Particular attention was given to the impact that both the length of the laser cavities and the mirror reflectivities have on laser operation across the temperature range. The optimal number of pairs in the top Distributed Bragg Reflector (DBR) was determined for stable operation at high temperatures and relatively high output powers. The effect on laser performance of expanding the metallization around the bottom DBR was also investigated.